A Human-Centered Design Framework for Intuitive Mobile AR in Medical Learning - Sattar, Mian Usman; Khan , Hamza Wazir; Khan , Hamza Wazir; Hassan , Raza; Hassan , Raza; Hassan, Atif (UMT Education Review, 2024)
Recent technological advancements have revolutionized the way individuals experience their surroundings. Emerging research has investigated the potential of utilizing Augmented Reality (AR) to enhance user experiences. This study examined the use of augmented reality applications to augment students’ intrinsic learning motivation. The research analyzed various factors influencing how augmented reality applications contribute to students’ intrinsic motivation. The study focused on the field of medicine, and the participants were medical students who participated in various surveys. Statistical t-tests were employed to compare the mean values of different learning methodologies. The statistical results showed the value of p=0.000, indicating that the results of this research are generalizable. The results showed an overall intrinsic motivation difference of 5.8 for augmented reality learning compared to text-based learning across competence, enjoyment, control, effort, value, and tension. These indicate statistically significant differences between the two learning methods. Finally, the study validated that the intrinsic motivation of medical students’ learning experience through augmented reality is higher than that of text-based learning.